Measuring Scientific Process Skills with Different Test Formats: A Research from the Perspective of Cognitive Styles - Sema Aydin-Ceran; Salih Ates (Journal of Education in Science, Environment and Health)
Considering that each student has a different cognitive structure, in addition to providing students with the perspective of a scientist, evaluating this acquisition; it is an important dimension of science education in the context of measurement and evaluation. In this context, the scientific process skills (SPS) of the students with different cognitive styles were examined and it was aimed to interpret the SPS measured in different test format according to cognitive styles. The study was a causal comparison and the study group consisted of 40 students at the seventh-grade level. Cognitive styles of the students were determined by using Group Embedded Figures Test. Open-ended, performance-based and multiplechoice tests were used to evaluate the scientific process skills. Criteria scales were used in the evaluation of open-ended and performance based SPS tests. The data were analyzed by MANOVA method which is a multivariate analysis of variance. Findings indicated that students with field independent cognitive style are more successful in multiple choice SPS test. However, it was concluded that there was no significant difference between mean scores of students in the fielddependent and field-independent cognitive style in both open-ended and performance-based SPS tests. Within the scope of the research, possible factors causing this result such as the difference of students' cognitive style tendencies, the test format used to measure scientific process skills, or the structure of the measured scientific process skills were discussed.